2020
DOI: 10.1101/2020.05.06.081505
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virome composition in marine fish revealed by meta-transcriptomics

Abstract: Identifying the components of host ecology that promote virus diversity is crucial for our understanding of the drivers of virus evolution and disease emergence. As the most species-rich group of vertebrates that exhibit diverse ecologies, fish provide an ideal model system to study the impacts of host ecology on the composition of their viromes. To better understand the factors that shape virome composition in marine fishes, we characterised the viromes of 23 fish species (19 from this study and four that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…A key observation of our study was the absence of Cyprinid herpesviruses, including CyHV-3, as well as other Alloherpesviridae, in any of the 36 RNA libraries. Similarly, although members of the Hepadnaviridae are commonly detected in fish [37,44,77,78] they were notably absent in our samples. The only DNA virus detected in this study was a novel poxvirus (Poxviridae) identified in western carp-gudgeon.…”
Section: Double-stranded Dna (Dsdna) Virusesmentioning
confidence: 51%
See 3 more Smart Citations
“…A key observation of our study was the absence of Cyprinid herpesviruses, including CyHV-3, as well as other Alloherpesviridae, in any of the 36 RNA libraries. Similarly, although members of the Hepadnaviridae are commonly detected in fish [37,44,77,78] they were notably absent in our samples. The only DNA virus detected in this study was a novel poxvirus (Poxviridae) identified in western carp-gudgeon.…”
Section: Double-stranded Dna (Dsdna) Virusesmentioning
confidence: 51%
“…Their abundance primarily impacts smaller native fish (such as carp-gudgeon, rainbowfish and hardyheads) since they typically outcompete these species and disrupt food webs [62]. As well as being highly divergent, western carpgudgeon arenavirus formed a basal clade with a recently discovered arenavirus in the pygmy goby sampled from an Australian coral reef [37], a member of the same fish order (Gobiiformes). These data further suggest that arenaviruses may have been circulating in Gobiiform fishes (gobies and gudgeons) in Australia prior to the introduction of eastern mosquitofish.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted February 8, 2021. ; https://doi.org/10.1101/2021.02.08.430315 doi: bioRxiv preprint 2 of 12 survey of vertebrates in China and is highly divergent from RuV, sharing around 34% nucleotide similarity [10]. Tiger flathead matonavirus was identified through a meta-transcriptomic exploration of Australian marine fish [11], which, along with Guangdong Chinese water snake rubivirus, forms a sister clade to RuV. Even more recently, two novel rubella-like virus species were described: Rustrela virus, identified in several mammalian species close by and in a zoo in Germany, and Ruhugu virus from bats in Uganda [12].…”
Section: Introductionmentioning
confidence: 99%